Multiple Studies: The Influence of Collaborative Learning Approach on Indonesian Secondary High School Students’ English-Speaking Skills - Berli Arta (English Language Teaching Educational Journal, 2018)
To respond the globalization, the importance of English communication skills including speaking skills increases. Looking at Indonesian context, secondary high school students find spoken English is much more difficult than written English. Students are good at grammar, reading, and writing but they can hardly speak (Hairdara, 2016). This article proposes collaborative learning approach (CLA) as one suitable solution to solve the obstacles of sharpening English speaking skills due to its benefits. The discussion of this investigation highlights some benefits of CLA in developing speaking skills and its challenges need to be considered as well. Receiving well-proven evidence of its benefits, CLA is recommended to be implemented in teaching and learning English speaking skills. As results of this investigation, there are three main benefits of CLA that its implementation can reduce language anxiety, raise students’ participation, and increase students’ self-confidence.